SIFAT FISIKA DAN MEKANIKA PAPAN LAMINASI KAYU SENGON DAN JATI PUTIH SEBAGAI SUBTITUSI KAYU SOLID - Febriana Tri Wulandari; Siti Latifah; Endah Wahyuningsih (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
This study aims to determine the physical and mechanical properties of sengon and white teak laminated boards, the effect of the weight of the coating, the type of wood and their interactions and the strength class of the laminated board. The physical and mechanical properties of sengon and white teak laminated boards are as follows: moisture content of 12.535%, density of 0.402 gram/cm³, thickness expansion of 1.544%, thickness shrinkage of 3.182%, MoE of 19745,840 kgf/cm², MoR of 330.106 kgf/cm². Laur weight did not significantly affect all physical and mechanical properties of sengon and white teak laminated boards except for water content testing. The type of wood had a significant effect on all tests of physical and mechanical properties of sengon and white teak laminated boards except for the MoE test. The interaction of wood species and pumpkin weight had no significant effect on all physical and mechanical properties tests except for water content and MoR tests. Based on the standards of SNI 03-2105-2006 and JAS 234-2007, all tests of physical and mechanical properties of sengon and white teak laminated boards have complied with the standard except for thick shrinkage and MoE tests. Based on the strength class of the laminated board, the laminated board of sengon wood and white teak is included in the strong class III which can be used as indoor construction materials.